Supply-side barriers to cross-border e-commerce in the EU Digital Single Market - Melisande Cardona; Bertin Martens (European Commission, Joint Research Centre (JRC), 2014)
Between 2009 and 2012 the percentage of online consumers in the EU who made online purchases in another EU Member State increased from 8 to 11 per cent, below the target of 20 per cent put forward in the EU Digital Agenda. Both, subjective perceptions on the consumer side or objective barriers on the supply side can play a role. This study uses a mystery shopping survey to measure the relative importance of supply side barriers. While 97 per cent of domestic orders lead to a successful shipment, we find that suppliers accepted to ship only 48 per cent of all cross-border online orders. This high failure rate may overstate the ordinary consumer experience because of the artificiality of the mystery shopping trade patterns. We therefore focus on the factors that drive success and failure. A shared language between buyer and supplier countries increased and size of the goods decreased the chances of success. Goods that are subject to geographical sales restrictions (vertical agreements) between producers, wholesalers and retailers are the least likely to be available for online cross-border orders. This may indicate that restrictions in competition in offline markets are spilling over to online markets and prevent the realization of some of the benefits of e-commerce. We conclude that regional integration in digital markets is constrained by the lack of integration in traditional bricks & mortar markets.
Keywords: 330; online trade; e-commerce; cross-border trade; barriers to trade; vertical constraints in online markets